Cathelicidin Host Defense Peptides and Inflammatory Signaling: Striking a Balance - Alford, Morgan A.; Baquir, Beverlie; Santana, Felix L.; Haney, Evan F.; Hancock, Robert E. W. (Frontiers in Microbiology, 2020)
Host-defense peptides (HDPs) are vital components of innate immunity in all vertebrates. While their antibacterial activity towards bacterial cells was the original focus for research, their ability to modulate immune and inflammatory processes has emerged as one of their major functions in the host and as a promising approach from which to develop novel therapeutics targeting inflammation and innate immunity. In this review, with particular emphasis on the cathelicidin family of peptides, the roles of natural HDPs are examined in managing immune activation, cellular recruitment, cytokine responses and inflammation in response to infection, as well as their contribution(s) to various inflammatory disorders and autoimmune diseases. Furthermore, we discuss current efforts to develop synthetic HDPs as therapeutics aimed at restoring balance to immune responses that are dysregulated and contribute to disease pathologies.